(untitled) (Journal of history, 2019)
Studying the horse harness of the early nomads of Kazakhstan is currently an urgent task, the solution of which will complement the characterization of the culture of the Saka-Scythian time. This article is devoted to the history of studying the complex of horse harness of the Scythian-Saka era. Common cultural and chronological definitions are used. The chronological framework of the study includes a transition period from bronze to iron (IX–VIII centuries BC), the Early Saka time (VIII–VI centuries BC), Saka (VI–IV centuries BC) and the final stage of the Pazyryk culture (IV–III centuries BC), which determines the ethnic connection and intercultural relations of tribes with adjacent regions. This period is characterized by the dynamic variability of horse harness. In general, details of horse harness are widely used in the construction of chronological scales, the reconstruction of migration processes in antiquity, etc. Detailed study and various analyzes of horse harnesses will help solve common and particular problems of archaeology of the Saka-Scythian time.